Participation in community based tank irrigation system in a rainfed region of India - T M, KIRAN KUMARA; KUMAR, SHIV; SINGH, DHARAM RAJ; IMMANUELRAJ, KINGSLY (The Indian Journal of Agricultural Sciences, 2018)
Tank irrigation is an important source of irrigation in rainfed region and has a less investment structure with few environmental problems. Despite several economic and environmental benefits, the performance of tanks has been poor due to lack of proper management and weak community participation. For effective management, the factors which affect the farmer’s participation need to be assessed. The study was undertaken in Andhra Pradesh and required data was collected through primary survey from farmers in Ananthapur and Chittor district for the agricultural year 2016-17. Principal component analysis and regression analysis were employed to analyze the data. The most important factors affecting farmer’s participation were farmer’s perceptions related to the water management system, tank structure, water accessibility and financial arrangement, explaining 72.8% of farmer’s participation in tank irrigation management. Further, level of farmers’ participation in tank irrigation management depends on increase in the net sown area, an increase in the need of irrigation water and cultivation of high water requirement crops, absence of membership in other organizations and increase in family size.